Determination of Proximate Composition, Phytochemical Content and Gut-health-promoting Efficacy of Developed Sorghum-based Functional Beverage - Pal, A. D.; Gandhi, R. (Journal of Scientific Research, 2024)
Considering the steady rise in gut-related issues worldwide, the study determined the nutritional composition, phytochemical content, and gut-health-promoting properties of a developed functional beverage containing Sorghum in combination with oats, barley, and whey versus the basic beverage (B) without Sorghum. Moreover, the functionality was assayed in vitro in a simulated human gastrointestinal environment to predict its efficacy in a human host. Variation 2 (V2), ranked highest through sensory acceptance (8.8), exhibited high fiber (43 %) and proteins (72.2 mg/dL), low reducing sugar and fat, a significant concentration of minerals (calcium, iron, and phosphorus), and phytochemicals (17.82 mg/dL alkaloids, 170.94 mgQE/dL flavonoids, and 85.5 mg GAE/dL polyphenols), which may propagate gut health. Moreover, V2 manifested potent antioxidant capacity (76.05 % DPPH radical inhibition and 35.2 µg/dL reducing potential) and prebiotic abilities, all of which may bestow gut-health promoting abilities. Interestingly, the phytochemical content and functional potentials were found to be retained even after an in vitro human gastrointestinal digestive treatment, indicating their effectiveness inside the human body. Therefore, intake of Sorghum in the form of V2 beverages may benefit gut health and supplement a healthy lifestyle owing to their biochemical composition and functional potential.